1986
DOI: 10.1177/009102608601500206
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Work Schedules, Productivity, Leave Usage, and Employee Attitudes: A Field Study

Abstract: Alternate work schedules reduced leave usage significantly during a nine month intervention time period in a government iigency. The effects of the change on individual productivity were mixed. Employee satisfaction with work schedules increased significantly, while other traditional satisfaction variables were not significantly affected by the work schedule intervention.η the past 15 years alternate work schedules (AWS), especially flexitime, have become widely used in business and government in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…In their comparison of the work motivations of public and private sector employees, Buelens and Van den Broeck (2007) found that public sector workers were more motivated by a desire to work in a supportive work environment. Positive relations between employees and their work colleagues (Kalleberg 1977) and supervisors (Harrick et al 1986) have been reported to raise employees' job satisfaction. Similarly, a positive correlation has been found between organizational commitment and employee-leader relations (Benkhoff 1997;Camilleri 2006;Dunham et al 1994).…”
Section: Organizational Influences Psm and Work Outcomes 71mentioning
confidence: 99%
“…In their comparison of the work motivations of public and private sector employees, Buelens and Van den Broeck (2007) found that public sector workers were more motivated by a desire to work in a supportive work environment. Positive relations between employees and their work colleagues (Kalleberg 1977) and supervisors (Harrick et al 1986) have been reported to raise employees' job satisfaction. Similarly, a positive correlation has been found between organizational commitment and employee-leader relations (Benkhoff 1997;Camilleri 2006;Dunham et al 1994).…”
Section: Organizational Influences Psm and Work Outcomes 71mentioning
confidence: 99%
“…Positive work relations with co-workers (Kalleberg 1977) and supervisors/ managers (Harrick et al 1986;Reiner and Zhao 1999) have been reported to raise job satisfaction. There is some empirical evidence that, compared to private sector employees, government workers show a stronger desire to work in a supportive working environment (Buelens and van den Broeck 2007); place a higher importance on their co-workers and superiors (Posner and Schmidt 1996); and respond more favorably to a people-oriented leadership style (Zeffane 1994).…”
Section: Work Relationsmentioning
confidence: 99%
“…For example, studies have shown that perceived organizational support is related to high organizational commitment, high satisfaction, and lower turnover Harrick, Vanek & Michlitsch, 1986;Schaffer, Harrison, Gilley & Luk, 2001;Thierry & Meijman, 1994;Thompson & Pottas, 2005). For example, studies have shown that perceived organizational support is related to high organizational commitment, high satisfaction, and lower turnover Harrick, Vanek & Michlitsch, 1986;Schaffer, Harrison, Gilley & Luk, 2001;Thierry & Meijman, 1994;Thompson & Pottas, 2005).…”
Section: The Role Of Social Support In the Relationship Between Work-mentioning
confidence: 99%